Diterpenoids and p-methoxycinnamic acid diol esters from Kaempferia saraburiensis Picheans. (Zingiberaceae): Structural assignment of saraburol and their biological activities. (July 2022) - Booranaseensuntorn, Pornpuk; Boonsombat, Jutatip; Mahidol, Chulabhorn; Reuk-Ngam, Nanthawan; Khlaychan, Panita; Batsomboon, Paratchata; Techasakul, Supanna; Thongnest, Sanit; Ruchirawat, Somsak
Abstract: Five undescribed compounds, including three diterpenoids namely, saraburol, saraburanes A and B, and two p -methoxycinnamic acid monoterpene diol esters, named E/Z -saraburinic esters, together with ten known oxygenated isopimarane diterpenoids, were isolated from the whole plant of Kaempferia saraburiensis Picheans. Among these compounds, saraburol possesses an unusual 6/9/6 tricyclic ring system bearing a 1, 3-dioxonane-4-one scaffold, which is rarely found in natural products. The structure of isolated compounds was elucidated by spectroscopic methods, including HRESIMS, FTIR, 1D and 2D-NMR, and by comparison with published data, and their absolute configurations were determined by comparison of experimental with calculated ECD spectra and hydrolysis reaction. Using gauge-independent atomic orbital (GIAO) NMR shift calculations coupled with DP4+ probability analyses, biogenetic considerations, and optical rotation allowed for the complete characterization of saraburol. A plausible biosynthetic pathway for saraburol and saraburane A was proposed. The cytotoxicity result indicated that E -saraburinic ester exhibited the most potent activity with an IC50 value of 12.0 μM against MOLT-3 cells with a selectivity index of 12.5. Saraburane B exhibited the most potent activity against Gram-positive bacteria strain Staphylococcus epidermidis with MIC (MBC) value of 25 (50) μg/mL. Graphical abstract: Five undescribed compounds, including three diterpenoids and two p -methoxycinnamic acid monoterpene diol esters, together with ten known diterpenoids, were isolated from Kaempferia saraburiensis Picheans. Image 1 Highlights: Fifteen compounds were isolated from Kaempferia saraburiensis. Five undescribed compounds including three diterpenoids and two p -methoxycinnamic acid esters. Saraburol featured with unusual 6/9/6 tricyclic ring bearing a 1, 3-dioxonane-4-one scaffold. A plausible biosynthetic pathway for saraburol and saraburane A was proposed. The structure-activity relationship (SAR) was described.